A contact mechanics interpretation of the duplex theory of tactile texture perception. (September 2016) - Fagiani, Ramona; Barbieri, Marco
Abstract: The tactile perception of a surface texture originates from scanning a finger on the surface. This kind of sliding contact activates the mechanoreceptors located into the skin, allowing the brain to identify the object and to perceive information about the scanned surface. Perception is collected by mechanoreceptors either by sensing pressure or by sensing vibration: the first mechanism is typical of large spaced surface textures, while the second is necessary to perceive finer textures. These different behaviors are well known in the literature as the duplex perception mechanism. In the present paper a numerical model describing finger-surface scanning is introduced in order to investigate the relationship between contact induced vibrations and scanning conditions. The model has been validated by experimental comparisons in a previous work. The perception model is used to develop a parametric analysis of the vibration induced from the finger-surface scanning as a function of surface geometry, scanning speed and contact force. The proposed parametric analysis points out the minimum number of parameters needed to describe the tactile perception of a periodic texture, and it shows the tribological reasons for which duplex perception mechanism is an effective biological evolution towards optimal tactile perception. Abstract : Highlights: Tactile perception of a periodic texture is modeled. The minimum number of dimensionless parameters affecting tactile perception of a periodic texture is found. The role of contact parameter is investigated and the optimal load for perception is pointed out. Evidence of the duplex perception mechanism: for largely spaced textures, the surface pattern is hidden in the vibration signal.